Comparison of Clinical Outcomes Between Posterior Instrumented Fusion With and Without Interbody Fusion for Isthmic Spondylolisthesis. Issue 1 (February 2021) - Chan, Vivien; Nataraj, Andrew; Bailey, Christopher; Abraham, Edward; Soroceanu, Alex; Johnson, Michael; Paquet, Jérôme; Christie, Sean; Stratton, Alexandra; Hall, Hamilton; Manson, Neil; Rampersaud, Y. Raja; et al.
Abstract : Study Design: A multicenter ambispective study using the Canadian Spine Outcomes and Research Network to compare clinical outcomes in adult patients with isthmic spondylolisthesis who received surgery. Objective: The purpose of this study is to compare 1-year postoperative clinical outcomes between posterior instrumented fusion with and without interbody fusion in patients with isthmic spondylolisthesis. Summary of Background Data: Despite the increased use of interbody fusion in patients with isthmic spondylolisthesis, clinical superiority has not been demonstrated. It remains unclear what the optimal surgical approach is for this population. Materials and Methods: The primary outcome was changed in leg pain at 1 year. Secondary outcomes were changed in Oswestry Disability Index, Short Form-12 Physical Component Score, and back pain at 1-year postoperative follow-up, estimated intraoperative blood loss, length of surgery, length of stay, number of transfusions, and adverse events. Descriptive statistics, Student t test, χ 2 test, and stepwise multivariable regression were used for analysis. Results: In total, 300 patients were included in this study. Of the 300 patients, 252 received posterolateral instrumented fusion with interbody fusion and 48 received posterolateral instrumented fusion alone. There were no significant differences in primary and secondary clinical outcomes at 1-year postoperative follow-up between the 2 groups. There were no significant differences in estimated blood loss (441 vs. 356 mL), length of surgery (210 vs. 224 min), length of stay (4 vs. 4 d), rate of transfusions (5.6% vs. 8.3%), and number of adverse events (33% vs. 23%) between patients who received interbody fusion and patients who did not. The addition of interbody fusion was not a significant variable for primary and secondary clinical outcomes in the stepwise multivariable regression analysis. Conclusions: There were no significant differences in clinical outcomes at 1 year or in the number of early complications between patients who received posterolateral fusion or posterior/transformational lumbar interbody fusion. Level of Evidence: Level III.